Growth performance, yield and quality of sweet potato [Ipomoea batatas (L.) Lam.] in response to different cropping systems - Ismail, Nur Arina (2019)
The production of sweet potato in Malaysia is low in which the cultivation is mostly operated by small-scale farmers who produce the crop far below the expected yield of the crop about 20 tons ha-1. A study was conducted to evaluate different cropping systems in terms of their interception of photosynthetically active radiation (PAR) and radiation use efficiency (RUE) on crop growth, yield potential and phytochemical contents of sweet potato. Study I consisted of four treatments with four replications; sole cropping sweet potato (Sole SP), sole cropping soybean (Sole SB), mixed intercropping sweet potato-soybean (Mixed SPSB) and relay intercropping sweet potato-soybean (Relay SPSB). Data from Study I evaluated the highest total dry matter (TDM) (13,560 kg haˉ1) and total crop yield (TCY) (4,770 kg haˉ1) were found in Mixed SPSB. However, the harvest index (HI) of Mixed SPSB (34.94%) was similar to Sole SP (38.82%) (p≤0.05). Mixed SPSB showed land equivalent ratio (LER) greater than 1 which means over yielding. No significant effect in maximum leaf area index (LAImax) of sweet potato in all treatments, however, a significant difference was reported in soybean in all cropping systems (p≤0.05). The critical leaf area index (LAIcrit) was achieved by sweet potato in Sole SP (4.17 at 96 day after sowing (DAS), Mixed SPSB (4.44 at 90 DAS) and Relay SPSB (4.85 at 108 DAS). The highest total PAR and RUE was shown by Sole SP (545.56 MJ m-2) and soybean in Mixed SPSB (1.40 g MJ-1), respectively. Implementation of different cropping systems of sweet potato with soybean did not influence the chromaticity values and phytochemical contents in sweet potato tubers. Study II consisted of seven treatments with four replications; sole cropping sweet potato (Sole SP), sole cropping soybean (Sole SB), sole cropping sweet corn (Sole SC), mixed intercropping sweet potato-soybean (Mixed SPSB), mixed intercropping sweet potato-sweet corn (Mixed SPSC), relay intercropping sweet potato soybean (Relay SPSB) and relay intercropping sweet potato-sweet corn (Relay SPSC). Data from Study II showed that sweet potato in Mixed SPSC gave the highest TCY (2,811 kg ha-1), LAImax (6.44) and RUE (1.90 g MJ-1). Sweet potato in mixed and relay intercropping were significantly higher in HI over Sole SP. The LAIcrit was found in sweet potato in Sole SP (3.92 at 72 DAS), Mixed SPSB (4.14 at 71 DAS) and Mixed SPSC (5.31 at 79 DAS). LER value was greater than 1 in mixed and relay intercropping, however, relay intercropping gave higher total PAR than mixed intercropping. Implementation of different cropping systems had no significant effect on chromaticity values of sweet potato tuber in all cropping systems (p≤0.05).The highest values of total phenolic content (0.33 mg GA g-1 FW), total flavonoid content (1.51 mg Quercetin g-1 FW), and antioxidant activity (57.21%) in sweet potato tuber in Mixed SPSB. As overall, the results indicated that mixed intercropping sweet potato with cereal crop gave the highest total crop yield compared to other treatments. The findings also showed that the phytochemicals found in sweet potato were influenced by different cropping systems.